LEVEL OF AWARENESS AND PARTICIPATION OF PANTAWID PAMILYANG PILIPINO PROGRAM BENEFICIARIES ON CLIMATE CHANGE ADAPTATION AND MITIGATION - Vidal, Amerjaphil Louie A.; Pedro, Anthony B. San; Redoble, Freyanne A.; Bermudez, Mildred M. (International Journal of Research -GRANTHAALAYAH, 2018)
This paper determined the level of awareness of Pantawid Pamilyang Pilipino Program (4Ps) beneficiaries on Climate Change and their level of participation in climate change adaptation and mitigation. The study is anchored on the Theory of Planned Behavior. The study utilized a descriptive survey method. The participants of the study are sixty-one (61) 4Ps Parent-Leaders from the twenty-two (22) barangays of Municipality of Llanera, Nueva Ecija. The results showed that 4Ps beneficiaries are aware of the effects of climate change but their participation to adapt and mitigate its effects are not always observed due to inadequate resources, technology and lack of support from the local government. The study showed the need to evaluate the 4Ps beneficiaries on the application of Family Development Session topics regarding Climate Change. The study may provide baseline data for the formulation of local policies and programs for participatory climate change adaptation and mitigation.